Anthracycline induced cardiac toxicity in pediatric Ewing sarcoma: A longitudinal study1. Issue 5 (4th February 2013) - Brown, Tanya Renae; Vijarnsorn, Chodchanok; Potts, Jim; Milner, Ruth; Sandor, George G.S.; Fryer, Christopher
Abstract Background Reports on incidence and factors associated with anthracycline cardiotoxicity in patients with Ewing sarcoma vary and few studies evaluate effect over time. Longitudinal trends in cardiac function and prognostic value of % decline in ejection fraction (EF) during therapy have not been previously described in Ewing sarcoma. Procedure A retrospective review of patients age <17 years, diagnosed with Ewing sarcoma during 1978–2006, treated at British Columbia Children's Hospital with anthracycline chemotherapy was undertaken. Echocardiograms performed pre‐treatment, worst function during treatment, on therapy completion; worst function during surveillance and the most recent echocardiogram were reviewed. Cardiac toxicity was graded using Common Terminology Criteria for Adverse Events v 3.0 and 4.0. Results Among 71 eligible patients, median age at diagnosis 11.1 years, median cumulative dose of anthracycline was 365 mg/m2. There were 397 echocardiograms with 153 (39%) abnormal. There were 21/71 patients with EF < 50%, 11 with EF < 40% and five cardiac deaths including 2/3 patients post‐cardiac transplant. The median time to worst cardiac function was 51 months. Post‐therapy completion 16/71 patients with progressive decline in cardiac function were noted. No patient with 10–15% decline in EF during therapy developed cardiotoxicity. Younger age (P = 0.004) and low BMI (P = 0.034) as continuous variables with anthracycline administration by IV push (P = 0.03) were risk factors for cardiotoxicity on univariate analysis but not significant within logistic regression models. Conclusions The high incidence of cardiotoxicity associated with higher administered anthracycline dose, young age, bolus infusion, and EF decline warrants evaluation in a larger cohort. Pediatr Blood Cancer 2013; 60: 842–848. © 2013 Wiley Periodicals, Inc.